1965
DOI: 10.1128/jb.89.5.1217-1224.1965
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of a Vi Antigen-Degrading Enzyme

Abstract: Vi antigen can be hydrolyzed by an inducible enzyme produced by a microorganism isolated from soil. The organism can be identified as Bacillus sphaericus. The enzyme in the culture supernatant fluid can be concentrated and partially purified by precipitation with ammonium sulfate at 50% of saturation. The partially purified enzyme is relatively stable. Incubation of the enzyme with V'i antigen causes a rapid loss of serological activity, a decrease in viscosity, the loss of ability to precipitate albumin at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1966
1966
1984
1984

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It seemed possible that the material remaining at the origin represented a core structure not attacked by the enzyme, since Baker and Whiteside (1965) observed that the enzyme did not bring about complete hydrolysis. Exhaustively degraded Vi antigen was concentrated on an Amicon filter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It seemed possible that the material remaining at the origin represented a core structure not attacked by the enzyme, since Baker and Whiteside (1965) observed that the enzyme did not bring about complete hydrolysis. Exhaustively degraded Vi antigen was concentrated on an Amicon filter.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes. The Vi antigen-degrading enzyme was isolated from cultures of B. sphaericus ATCC 17932, by the method of Baker and Whiteside (1965). Vi enzyme assays were carried out at 40°with the substrate in a standard buffer containing 0.033 m Tris (pH 8.2) and 1 mM CaCl2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deacetylated Vi was obtained by treating Vi with 0.1 N NaOH at room temperature (15). Enzymatically degraded Vi was made by the procedure previously described (2). O antigen was prepared from water extracts of acetonekilled S. typhosa 0-901.…”
Section: Methodsmentioning
confidence: 99%
“…Hydrolyzing N-Acetylglucosaminyl Ribitol Teichoic Acid-Peptidoglycan Complex The methods essentially followed those of Baker and Whiteside [2] and Kotani et al [14], used for isolating soil bacteria degrading Vi antigen and serologically active mycobacterial and corynebacterial polysaccharides, respectively. Soil specimens were incubated at 29 C and pH 7.2 in a minimal medium containing 0.1% (NH4)2SO4, 0.2% K2HPO4, 0.0005% MgSO4.7H20 and S. aureus cell wall lysate [ref.…”
Section: Isolation From Soil Of a Microorganism Capable Ofmentioning
confidence: 99%